A companion to ancient Greek and Roman music - Lynch, Tosca; Rocconi, Eleonora (Wiley, 2020)
Mythical Paradigms. The Mythology of the Muses / Penelope Murray ; Apollo and Music / Ian Rutherford ; Dionysus and the Ambiguity of Orgiastic Music / Giorgio Ieranò ; Pan and the Music of Nature / Pauline LeVen ; Musical Heroes / Susanna Sarti ; Musical Metamorphoses in the Roman World / Luigi Galasso -- Contexts and Practices. Ancient Musical Performance in Context : Places, Settings and Occasions / Sylvain Perrot ; Documenting Music / Maria Chiara Martinelli ; Visualizing Music / Sheramy Bundrick ; Music in Classical Greek Drama / Marco Ercoles ; Music in Roman Drama / Timothy J. Moore ; Ancient Greek Choreia / Naomi A. Weiss ; Roman Dance / Zoa Alonso Fernández ; Musical Competitors and Competitions in Greece and Rome / Timothy Power ; The Vocal Art in Greek and Roman Antiquity / Kostantinos Melidis ; Musical Instruments of Greek and Roman Antiquity / Chrestos Terzēs ; Ancient Greek Music and the Near East / John Franklin -- Conceptualising Music : Musical Theory and Thought. Acoustics / Egert Pöhlmann ; Harmonics / Andrew Barker ; Rhythmics / Tosca A.C. Lynch ; Notation / Stefan Hagel ; Music in Greek and Roman Education / Massimo Raffa ; Musical Aesthetics / Eleonora Rocconi ; Music and Emotions / Francesco Pelosi ; Music and Medicine / Antonietta Provenza ; The Music of the Words in Roman Rhetoric / Verena Schulz ; Music and Society : Musical Identities, Ideology and Politics. Between Local and Global : Music and Cultural Identity in Ancient Greece / Mark Griffith ; Music and Gender in Greek and Roman Culture : Female Performers and Composers / Mariella De Simone ; 'Old' and 'New' Music : The Ideology of Mousikē / Armand D'Angour ; The Politics of Theater Music in Fifth- and Fourth-Century Greece / Eric Csapo and Peter Wilson ; Music, Power and Propaganda in Julio-Claudian Imperial Rome (27 BC-68 AD) / Paola Dessì -- 'Rediscovering Ancient Music' : The Cultural Heritage of Mousikē. The Reception of Greek Musical Theory in the Middle Ages : Boethius and the Depictions of Ancient Musicians / Cecilia Panti ; Ancient Greek Music in Early Modern Italy : Performance and Self-Representation / Donatella Restani ; The Visual Heritage : Images of Ancient Music before and after the Rediscovery of Pompeii / Daniela Castaldo -- Appendix. Diagrams of the Ancient Modes (Harmoniai) as Aulos and Lyre Tunings / Tosca A.C. Lynch.
Includes bibliographical references and index